2016
DOI: 10.1128/jcm.03107-15
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Bruker MALDI Biotyper for Identification of Fastidious Gram-Negative Rods

Abstract: Matrix-assisted laser desorption ionization؊time of flight mass spectrometry (MALDI-TOF MS) has entered clinical laboratories, facilitating identification of bacteria. Here, we evaluated the MALDI Biotyper (Bruker Daltonics) for the identification of fastidious Gram-negative rods (GNR). Three sample preparation methods, direct colony transfer, direct transfer plus on-target formic acid preparation, and ethanol-formic acid extraction, were analyzed for 151 clinical isolates. Direct colony transfer applied with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 34 publications
(44 reference statements)
3
24
1
Order By: Relevance
“…Reduction of cutoff scores was particularly beneficial for the Gram‐positive organisms, with a 10.3% increase noted at ≥1.9 cutoff compared to 3.6% for the Gram‐negative organisms ( P = 0.0001). Of the discrepant results, 20 viridans group streptococci were misidentified as Streptococcus pneumonia , which is not surprising as similar findings have been previously reported in the literature . Thus, omission of these 20 isolates dramatically increased the species‐level identification rate of Gram‐positive organisms from 84.8% to 95.7% at a ≥1.9 cutoff.…”
Section: Resultssupporting
confidence: 73%
See 2 more Smart Citations
“…Reduction of cutoff scores was particularly beneficial for the Gram‐positive organisms, with a 10.3% increase noted at ≥1.9 cutoff compared to 3.6% for the Gram‐negative organisms ( P = 0.0001). Of the discrepant results, 20 viridans group streptococci were misidentified as Streptococcus pneumonia , which is not surprising as similar findings have been previously reported in the literature . Thus, omission of these 20 isolates dramatically increased the species‐level identification rate of Gram‐positive organisms from 84.8% to 95.7% at a ≥1.9 cutoff.…”
Section: Resultssupporting
confidence: 73%
“…While extraction of cellular content prior to analysis by MALDI‐TOF MS increases spectral scores and the rate of species‐level identification , it involves additional hands‐on steps, which can become laborious for the CLS performing batch setup of multiple isolates , increasing the preparation and identification time by up to fivefold per specimen . Previous studies have demonstrated that although the direct‐smear method is sufficient for Gram‐negative bacteria identification to the species level, the yield for species‐level identification of Gram‐positive is low and typically requires an extraction step . In this study, we successfully demonstrated that identification of aerobic Gram‐positive and Gram‐negative organisms could be performed accurately and efficiently by MALDI‐TOF MS and Bruker Biotyper system using the direct‐smear method alone and a decreased score of ≥1.9 for species‐level identification of both Gram‐negative and Gram‐positive organisms.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Nonetheless, there have been reports that some isolates are identified correctly by means of low Score Values, whereas some others are misidentified via a high Score Value (5-7). Lower species cutoffs that may offer an optimal balance between an increased number of correct identifications and a limited number of misidentifications have been suggested in some reports (8)(9)(10). In our case, however, N. cinerea was misidentified as N. meningitidis with the Score Value above 2.0 (i.e., 2.024).…”
mentioning
confidence: 50%
“…All isolates were identified to the species level. Sample preparation and analysis were done as described previously (56). Mass spectra were acquired and analyzed using a microflex LT mass spectrometer (Bruker Daltonics) in combination with research use only version of the MALDI Biotyper Compass software 4.1 and the reference database MBT 7311 MSP Library (no.…”
Section: Methodsmentioning
confidence: 99%